(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article is devoted to the problem of developing critical thinking in the modern educational system. The paper analyzes the relationship between the development of critical thinking and humane pedagogy. The work aims to systematize the methods that contribute to the development of this type of thinking in the context of humane pedagogy. The study uses the works of researchers such as Kluster, S. I. Zair-Bek and I. V. Mushtavinskaya, R. Pole and L. Elder, M. Lipman, R. Ennis, Sh. A. Amonoshvili, and others.